Electromagnetic-pulse-induced acoustic testing for nondestructive testing of plastic composite/metal adhesive bonding. (6th November 2020) - Sun, Hongjun; Kosukegawa, Hiroyuki; Hashimoto, Mitsuo; Uchimoto, Tetsuya; Takagi, Toshiyuki
Abstract: For the hydrogen tanks of type 2 and 3, the metal lining and composite wrapping are bonded together by adhesive. To ensure the safety of these tanks for long-term use, nondestructive testing (NDT) and nondestructive evaluation (NDE) of their plastic composite/metal adhesive bonds are required. However, up to now, there is no effective NDT method for the debonding detection of hydrogen tanks of type 2 and 3. In this study, we propose the use of electromagnetic-pulse-induced acoustic testing (EPAT) to generate guided waves in plastic composite/metal adhesive bonding to detect debonding in adhesive parts. The EPAT method can excite the electromagnetic force from outside of the plastic composite material without contact, thereby directly exciting sound waves on the metal contacting the plastic composite. Through reasonable design, the intensity of the pulsed magnetic field can pass through a very thick plastic composite material and directly induces guided waves in the inner side metal. Therefore, EPAT method has the potential to detect the debonding of plastic composite/metal adhesive bonding in hydrogen tanks of type 2 and type 3 at the site of use. EPAT testing of acrylic/aluminum, glass-fiber-reinforced plastic/aluminum, and carbon-fiber-reinforced plastic/aluminum specimens was performed. The testing signals were analyzed in the time domain and frequency domain. The results indicate that the time-domain signals exhibited guided wave dispersion characteristics. In addition, the guided wave signals showed significant differences between the specimen with debonding and that without debonding, which could be used for the detection of debonding. In addition, different frequency guided waves had different sensitivities to debonding defects. Highlights: Electromagnetic-pulse-induced acoustic testing (EPAT) method is proposed. EPAT method can induce guided waves in the inner side metal without contact. EPAT method has the potential to detect the debonding in hydrogen tanks.